Optimization of Low Site Density Area for 4G Network in Urban City - Hajiar Yuliana; Sofyan Basuki; Salita Ulitia Prini (Jurnal Elektronika dan Telekomunikasi, 2021)
The development of telecommunications is currently growing rapidly, especially in urban areas. To obtain optimal data services for users, the performances of 4G network services must continue to be optimized. It is known that many users are scattered in urban areas, but sometimes it is not balanced with an even distribution of the site in this area. This condition occurs because the distribution of the site is not evenly optimal distributed, either due to licensing constraints, limited land access for site development, or in terms of plans that have not been made. Balanced with the requirement of a 4G network, which is required, this "empty space" condition or low site density condition must find a solution or optimize it. Many optimization methods can optimize the area with low site density possibility. This study will optimize the area by adding a new site proposal based on coverage planning. We need to analyze Reference Signal Received Power (RSRP) coverage signal distribution using Atoll Planning Software. After optimization, the RSRP level below or equal -80 dBm increased from 75.195% to 94.08%. Furthermore, the percentage calculation for inadequate coverage (below -80 dBm) decreased from 24.816% to 5.931%. This RSRP signal level also shows that the condition after optimization with a new site can improve the signal level condition from areas with low site density possibility.